2008
DOI: 10.1080/22201173.2008.10872572
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomised comparison of continuous paravertebral block and continuous intercostal nerve block for post-thoracotomy pain

Abstract: Background: This study aimed to compare paravertebral block and continuous intercostal nerve block after thoracotomy. Methods: Forty-six adult patients undergoing elective posterolateral thoracotomy were randomised to receive either a continuous intercostal nerve blockade or a paravertebral block. Opioid consumption and postoperative pain were assessed for 48 hours .Pulmonary function was assessed by forced expiratory volume in 1 s (FEV1) recorded at 4 hours intervals. Results: With respect to the objective vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
(35 reference statements)
1
3
0
3
Order By: Relevance
“…The VAS on coughing at 8 hours after surgery between PVB and INB reported in Chen et.al [ 14 ] had significant difference. There was also a significant difference in the VAS on coughing at 24hours and 48 hours after operation reported by Ouerghi et.al [ 20 ] and the VAS on coughing at 1hour and 2 hour after operation reported by Chen et.al [ 19 ], and the other studies included did not find any differences in the VAS on coughing in each period of time.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The VAS on coughing at 8 hours after surgery between PVB and INB reported in Chen et.al [ 14 ] had significant difference. There was also a significant difference in the VAS on coughing at 24hours and 48 hours after operation reported by Ouerghi et.al [ 20 ] and the VAS on coughing at 1hour and 2 hour after operation reported by Chen et.al [ 19 ], and the other studies included did not find any differences in the VAS on coughing in each period of time.…”
Section: Discussionmentioning
confidence: 72%
“…We used the random-effect model to analysis the outcome of postoperative use of morphine in three trials Hutchins (2017), Perttunen (1995) and Ouerghi (2008) [ 18 , 20 , 21 ]. The results showed that compared to INB, PVB can result in a significantly decrease in postoperative morphine (Std.…”
Section: Resultsmentioning
confidence: 99%
“…Para la técnica de BPV-AS (n = 393), la media de dolor en EVA fue menor o igual a 4 en el POP inmediato en los estudios que lo reportaron, al igual que en las 6, 12, 24 y 48 horas posoperatorias en casi todos los estudios, excepto en el de Ouerghi et al 21 y Kosisnski et al, 26 en los cuales el dolor POP tuvo alta variabilidad. Ambos estudios compararon el bloqueo epidural frente al BPV-AS, encontrando diferencia a favor del epidural.…”
Section: Síntesis De Los Resultadosunclassified
“…En la Figura 4 se muestra el resumen de consumo de morfina para las técnicas en el POP, y en el Anexo 5 (CDC) el reporte de consumo de morfina para cada estudio. Solo en 8 de los estudios donde se realiz o el BVP-AS fue posible determinar el consumo de opioides en equivalentes de morfina, 18,[21][22][23]26,27,30,31 en los cuales se emple o catéter paravertebral como técnica analgésica POP.…”
Section: Síntesis De Los Resultadosunclassified
See 1 more Smart Citation